IMPLIKASI CHILDFREE TERHADAP HAK WARIS DALAM KELUARGA ISLAM - Fatah, Nasrul; Nasrul Fatah; Syarifah Laili; Khairunnas Jamal; Hendri Sayuti (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
The phenomenon of childfree, namely the conscious decision not to have offspring, is a contemporary social dynamic that impacts the Islamic family law system, particularly in the area of inheritance. This study aims to analyze how the choice of childfree affects the structure of inheritance rights in Islam and how the maqashid shari’ah approach can be employed to address these changes. Employing normative legal research methods with theological, conceptual, and maqashid shari’ah approaches, the study finds that the absence of descendants due to a childfree decision shifts the inheritance structure to horizontal relatives or the public treasury (Baitul Mal). Instruments such as wills (wasiyyah) and grants (hibah) play a crucial role in regulating the distribution of estates in this context. The study concludes that although childfree alters the traditional family structure, the principles of justice, property protection, and social sustainability can still be upheld within the Islamic legal framework through a maqashid shari’ah-based reinterpretation. Therefore, strengthening legal literacy and adjusting regulations are essential to address this phenomenon fairly and in line with Islamic objectives